1993
DOI: 10.1097/00005373-199309000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokines Following Thermal Injury and Their Relationship With Patient Mortality, Burn Size, and Time Postburn

Abstract: We measured plasma levels of interieukin-1l6 (IL-1j5), tumor necrosis factor a (TNFa), and interdeukin-6 (IL-6) following thermal injury. Cytokine levels In the plasma of 27 burned patients were serially screened by ELISA and compared with cytokine levels > in 16 healthy laboratory employees. The relationships between cytokine_ (.0 concentrations and patient mortality, bum size, and time postbum were examined. Plasma samples with detectable amounts of IL-1ft and IL-6 were significantly more frequent in burned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(84 citation statements)
references
References 0 publications
5
77
0
2
Order By: Relevance
“…A significant increase in circulating levels of IL-6 was observed at 2-18 h post-injury, consistent with previous observations [31,32]. A trend toward lower plasma IL-6 levels in TCR ␦ -/-mice was observed, however, statistical significance was not achieved.…”
Section: Discussionsupporting
confidence: 91%
“…A significant increase in circulating levels of IL-6 was observed at 2-18 h post-injury, consistent with previous observations [31,32]. A trend toward lower plasma IL-6 levels in TCR ␦ -/-mice was observed, however, statistical significance was not achieved.…”
Section: Discussionsupporting
confidence: 91%
“…An important player in any inflammatory response, IL-6 is particularly elevated in thermally injured patients (54,60) and correlates to increased mortality risk after injury (14). Moreover, we and others have reported that antecedent intoxication significantly raises IL-6 levels of burn-injured mice (8,10,32) and that reduction of IL-6 attenuates pulmonary inflammation (7) and gut permeability (61), possibly serving as a link between the gut, liver, and lung in this common clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…17,28,29 TNF-α has been demonstrated to play a major role in the pathogenesis of sepsis and its complications after burn injury. [30][31][32][33] Furthermore, there is evidence that a guanine to adenine substitution (G→A) at nucleotide -308 within the TNF-α promoter affects transcriptional regulation. 34,35 Carriage of the A-allele at this position has been associated with altered transcription and increased risk for infectious and inflammatory diseases in a number of clinical settings, including acute graft rejection following renal transplantation, sepsis among trauma patients, acute malaria and death from meningococcal disease.…”
Section: Discussionmentioning
confidence: 99%